Dynamic Changes of Gut Microbiome in Borneo Earless Monitor Lizard Across Different Diets - Diana, Milsa Solva; Fitri, Ainissya; Anja, Meryandini; Ridwan, Roni (HAYATI Journal of Biosciences, 2025)
The Borneo earless monitor lizard (Lanthanotus borneensis) is one of the endemic animals of Indonesia. In 2019, the IUCN listed L. borneensis as an ‘endangered’ species. The declining population of the L. borneensis is a major concern for conservation efforts. One of the efforts to conserve endangered wild animals is to know the gut microbiome profile and the relationship between the host and the bacterial community in the body, which is associated with an influence on health. This research aims to determine the gut microbiome profile of animals with metagenomic analysis using Next-Generation Sequencing (NGS). This research was carried out by providing three feed types: earthworms, shrimp, and fish. Sample feces was collected by cloacal swabs and the DNA was sequenced using the Illumina NGS technique in the V4 16S rRNA region to examine the gut microbiome. The results of the metagenomic analysis showed differences in bacterial abundance in each feed treatment. The L. borneensis treated with earthworms and fish were dominated at the phylum level by Proteobacteria and Bacteriodota, while in shrimp, the phyla were Proteobacteria and Firmicutes. Index Shanon, Simpson, and the rarefaction curve also showed the highest bacterial diversity found in the fish treatment. This study can be used as a reference in designing suitable feed formulations for effective captive breeding for the conservation of L. borneensis